Computer vision, imaging and computer graphics theory and applications : 10th International Joint Conference, VISIGRAPP 2015, Berlin, Germany, March 11-14, 2015, Revised selected papers /: 10th International Joint Conference, VISIGRAPP 2015, Berlin, Germany, March 11-14, 2015, Revised selected papers. (2016) - Unknown
No abstract available